2015
DOI: 10.1016/j.jaac.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparative Trial of a Social Cognitive Skills Group for Children With Autism Spectrum Disorder

Abstract: Objective This study evaluated the efficacy of a targeted social skills training group in school-aged children with autism spectrum disorder (ASD). The intervention, NETT (Nonverbal communication, Emotion recognition, and Theory of mind Training), is a 12-session cognitive-behavioral intervention (CBI) for verbal, school-aged children targeting ASD-specific social behavioral impairments. Method Sixty-nine children with ASD, 8 to 11 years of age with verbal IQs greater than 70, participated in a randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 38 publications
2
62
0
6
Order By: Relevance
“…The week 11 results reported by Minshawi et al demonstrating decreased SRS total scores in both treatment groups but not between group treatment effects align with previous reports of substantial immediate impact of social skills training in youth with ASD [2]. In this follow-up study, we show enhanced durability of treatment response in those subjects who received weekly DCS, a novel finding considering previous studies indicating lack of treatment durability following social skills intervention in ASD [4]. In this analysis, DCS appears to support maintenance of social skills gains made during short-term group therapy compared to placebo.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The week 11 results reported by Minshawi et al demonstrating decreased SRS total scores in both treatment groups but not between group treatment effects align with previous reports of substantial immediate impact of social skills training in youth with ASD [2]. In this follow-up study, we show enhanced durability of treatment response in those subjects who received weekly DCS, a novel finding considering previous studies indicating lack of treatment durability following social skills intervention in ASD [4]. In this analysis, DCS appears to support maintenance of social skills gains made during short-term group therapy compared to placebo.…”
Section: Discussionsupporting
confidence: 90%
“…Social skills training explicitly targets this core deficit and is widely implemented in ASD treatment [2]. Adolescent social skills groups consistently demonstrate immediate improvements in social and communication skills in participants during treatment; however, participants tend to show limited sustained treatment response over longer term follow-up [24]. …”
Section: Introductionmentioning
confidence: 99%
“…With regards to treatment research, the RMET is widely used as treatment outcome measure, particularly for drug manipulations (i.e. oxytocin) or behavioral interventions targeting social skills and social cognition (e.g., [32][33][34][35] ). All of this prior work utilizes an analytic strategy of computing RMET summary scores across all items and then onto potentially sub-optimal omnibus case-control comparisons which mask the presence of nested subgroups within ASC.…”
Section: Discussionmentioning
confidence: 99%
“…The RMET is widely used as a core instrument for assessing difficulties in the social cognitive domain of understanding other minds, and its prominence has even warranted its listing as a core instrument in this domain within the NIMH RDoC (http://1.usa.gov/1Qs6MdI). The RMET is also widely utilized as a treatment outcome measure (e.g., [32][33][34][35]. Given that inconsistency exists behind findings from mentalizing-based treatments for ASC 36 and the tacit understanding that heterogeneity in treatment response is highly likely, it is critical to further our understanding of how mentalizing heterogeneity manifests in ASC, particularly on the RMET, and whether such insights can help in better trial design and/or in individualizing interpretations about who may benefit from such treatments.…”
mentioning
confidence: 99%
“…A recent study in ASD adolescents found that combined poor performance on several social cognition tasks (ToM tasks, emotion-recognition tasks, and anthropomorphic animations) was collectively associated with elevated SRS score (64). Some ASD studies have further found that parent/caregiver report of real-world social behaviors are better measures of treatmentrelated changes in social outcomes than are social cognition tasks, which suggests that these tasks may be measuring more nuanced social cognition skills such as ToM or attribution of intentions compared to every-day reciprocal social behaviors assessed by the SRS (65,66). Hence, it is possible that the types of social concerns endorsed on the SRS (e.g., eye contact, odd behaviors, preference for being alone, ritualistic behaviors) may not relate as closely as we originally hypothesized to the TASIT's measurement of nuanced social cognition skills such as lie and sarcasm detection.…”
Section: Discussionmentioning
confidence: 99%